Effect of Ralgro® on performance of steers grazing high and low endophyte fungus-infested tall fescue pastures - Brazle, F.K. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Steers were either not implanted or implanted with 36 or 72 mg of Ralgro, then allowed to graze on both high and low endophyte fungus tall fescue pastures. Ralgro had a greater effect on improving gains of steers grazing high endophyte fungus pastures than on those grazing lowly infected fescue pastures.
Keywords: Beef; Ralgro®; Performance; Steers; Endophyte; Fescue